Efficacy and safety of endoscopic ultrasound-guided hepaticogastrostomy: a meta-regression analysis - Binda, Cecilia; Dajti, Elton; Giuffrida, Paolo; Trebbi, Margherita; Coluccio, Chiara; Cucchetti, Alessandro; Fugazza, Alessandro; Perini, Barbara; Gibiino, Giulia; Anderloni, Andrea; Repici, Alessandro; Fabbri, Carlo (Endoscopy, 2024)
Background Endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) is a valid option for EUS-guided biliary drainage that has been increasingly used in the last decade. The aims of this study were to provide a systematic review with meta-analysis and meta-regression of the features and outcomes of this procedure.Methods The MEDLINE, Scopus, Web of Science, and Cochrane databases were searched for literature pertinent to EUS-HGS. Meta-analysis of the proportions and meta-regression of potential modifiers of the main outcome measures were applied. The main outcome was technical success; secondary outcomes were clinical success and procedure-related adverse events (AEs).Results 33 studies, including 1644 patients, were included in the meta-analysis. Malignant biliary obstruction (MBO) was the underlying cause in almost all cases (99.6%); the main indications for EUS-HGS were duodenal/papillary invasion (34.8%), surgically altered anatomy (18.4%), and hilar stenosis (16.0%). The pooled technical success of EUS-HGS was 97.7% (95%CI 96.1%–99.0%; I2 = 0%), the intention-to-treat clinical success rate was 88.1% (95%CI 84.7%–91.2%; I2 = 33.9%), and procedure-related AEs occurred in 12.0% (95%CI 9.8%–14.5%; I2 = 20.4%), with cholangitis/sepsis (2.8%) and bleeding (2.3%) the most frequent. The rate of procedure-related AEs was lower with the use of dedicated stents on univariable meta-regression analysis. Meta-regression showed that technical success and clinical success rates were modified by the centers’ experience (>4/year).Conclusions EUS-HGS represents an effective and safe procedure for EUS-guided biliary drainage in patients with MBO. Future studies should address the impact of center experience, patient selection, and the use of dedicated stents to improve performance of this technique.